FACTORIAL DESIGN DEVELOPED BIOPOLYMER NANOPARTICLES FOR ORAL DELIVERY OF INSULIN - Antonio Ribeiro; Bruno Pessoa (LIFE: International Journal of Health and Life-Sciences, 2026)
The development of chitosan-coated alginate/dextran sulphate nanoparticles for insulin encapsulation is addressed. Nanoparticles are produced by ionotropic gelation followed by polyelectrolyte complexation. The objective of this study is to optimize chitosan-based biopolymer nanoparticles for the oral delivery of insulin using a quality-by-design (QbD) approach. Four input factors are considered: Concentrations of alginate /dextran sulfate, chitosan, poloxamer, and insulin, together with process parameters, flow rate (ml/min) and agitation speed rate during chitosan addition were the input factors considered. Critical quality attributes include particle size, polydispersity index, zeta potential, and encapsulation efficiency. The implemented built-quality method follows three successive QbD runs, each based on a specific design of experiments (DoE). First, a screening of the material attributes is performed using a fractional factorial design, followed by a second run using a Box-Behnken design to identify the design space and extract four eligible control operating regions in which the probability of meeting the CQA specifications exceeds 95%. In the last run, one of these optimal operating conditions was qualified by testing eight endpoints across the region using a full factorial design.